Laser Erasing and Rewriting of Flexible Copper Circuits - Xingwen Zhou (Nano-Micro Letters, 2021)
Abstract Integrating construction and reconstruction of highly conductive structures into one process is of great interest in developing and manufacturing of electronics, but it is quite challenging because these two involve contradictive additive and subtractive processes. In this work, we report an all-laser mask-less processing technology that integrates manufacturing, modifying, and restoring of highly conductive Cu structures. By traveling a focused laser, the Cu patterns can be fabricated on the flexible substrate, while these as-written patterns can be selectively erased by changing the laser to a defocused state. Subsequently, the fresh patterns with identical conductivity and stability can be rewritten by repeating the writing step. Further, this erasing–rewriting process is also capable of repairing failure patterns, such as oxidation and cracking. Owing to the high controllability of this writing–erasing–rewriting process and its excellent reproducibility for conductive structures, it opens a new avenue for rapid healing and prototyping of electronics.